Study of parameters for bioethanol production from Baltic Sea macroalgae - Sukhikh, Stanislav; Ivanova, Svetlana; Babich, Olga; Davydova, Anastasia; Sirohi, Ranjna; Michaud, Philippe; Dolganyuk, Vyacheslav; Kriger, Olga (Bioresource technology reports, 2023)
This study aimed to investigate the possibility of producing biofuels from Baltic Sea macroalgae. The scientific value of the article consists in the adaptation of known methods of bioethanol production from seaweeds of the Baltic Sea, selection of processing parameters and bioconversion of macroalgae biomass. Capillary sequencing using amplicon cloning identified four species of macroalgae collected on the coast of the Baltic Sea: Ulva clathrata, Ulva prolifera, Cladophohora fracta, and Ulva intenstinalis. Cellulase and xylanase enzymes, as well as microorganisms Saccharomyces cerevisiae, Lachancea thermotolerans, Pachysolen tannophilus were used to treat macroalgae biomass. Before macroalgae fermentation, acid, alkaline, and enzymatic pretreatments were performed. It was found that bioethanol can be extracted from Baltic Sea macroalgae samples using any of the processing methods considered, but alkaline pretreatment yielded the highest content of 32 %. The Baltic Sea macroalgae can be a potential source of bioethanol, which are alternatives to hydrocarbon fuels.